Tetanus Toxoid Vaccination Status of Women of child bearing age in Rangamati Pourashava - Nazneen, Nazia; Alam, Mohammed Nurul; Akhter, Most Dalia; Rahman, Md Shamsur; Parveen, Mukta; Begum, Arifa (Mediscope, 2021)
Tetanus Toxoid (TT) is a routine vaccination activity under Expanded Program on Immunization (EPI) in Bangladesh. This was a descriptive type of cross-sectional study with a sample size of 110, selected purposively by non-probability sampling technique. Data were collected through a pretested questionnaire. The aim of this study was to assess TT vaccination coverage among the women of child bearing age, Rangamati Pourashava. As per survey, among 110 respondents, 29 (26.4%) were of 15-25 years, 52 (47.3%) were of 26-35 years, 25(22.7%) were of 36-45 years & only 4(3.6%) were of >45years. In this study, the major group, 86(78.2%) were married, 17(15.4%) were unmarried & only 7 (6.4%) were widow. Most of the respondents considered vaccination as the way of disease prevention, so that the coverage being 92 (83.6%) in case of TT vaccination. It was found that 70% women received TT vaccine from Government EPI centers followed by 23.6% from NGO facilities and only6.4% from private clinics. Among the respondents, 56.3% respondents had completed their dose schedule of TT vaccine respectively. Most of the respondents had their vaccination card. The percentage was 70 for TT respectively. Among others, 20% failed to follow it because of forgetfulness of doses and 3.34% because of losing their card. So, TT vaccination coverage among the women of child bearing age was satisfactory but it also suggests that more awareness campaign for vaccination is sensational among the mass people of our country. This study TT vaccination status among women of child bearing age will help to get idea about the woman of our country regarding the situation. Mediscope Vol. 8, No. 1: January 2021, Page 40-44